2015
DOI: 10.1017/s0272263114000606
|View full text |Cite
|
Sign up to set email alerts
|

How Does Prior Word Knowledge Affect Vocabulary Learning Progress in an Extensive Reading Program?

Abstract: Sixty English as a foreign language learners were divided into high-, intermediate-, and low-level groups based on their scores on pretests of target vocabulary and Vocabulary Levels Test scores. The participants read 10 Level 1 and 10 Level 2 graded readers over 37 weeks during two terms. Two sets of 100 target words were chosen from each set of graded readers and were tested on three occasions. The results showed that the relative gains from pretest to immediate posttest were 63.18%, 44.64%, and 28.12% for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 39 publications
6
100
2
Order By: Relevance
“…A large number of target items that differed in a number of ways (see Table ) were selected to capture as much incidental learning as possible. Such an approach “may provide a more accurate representation of vocabulary learning gains than frequency‐based selection of items” (Webb & Chang, , p. 658). Fifteen items had imagery support; 21 items were not supported by on‐screen imagery.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of target items that differed in a number of ways (see Table ) were selected to capture as much incidental learning as possible. Such an approach “may provide a more accurate representation of vocabulary learning gains than frequency‐based selection of items” (Webb & Chang, , p. 658). Fifteen items had imagery support; 21 items were not supported by on‐screen imagery.…”
Section: Methodsmentioning
confidence: 99%
“…Given this, the graded readers were suitable for the student's English proficiency. More importantly, these graded readers had been used many times by previous students who had similar vocabulary knowledge and were usually reported as quite easy and interesting (Webb & Chang, 2014, 2015. The average of each audio duration was about 1 h per book.…”
Section: The Study Materials and Lexical Profilesmentioning
confidence: 99%
“…Studies of extensive reading have identified positive impacts of extensive reading on L2 reading abilities and vocabulary (e.g., Al‐Homoud & Schmitt, ; Beglar, Hunt, & Kite, ; Horst, ; Mason & Krashen, ; Pigada & Schmitt, ; Webb & Chang, ). However, positive results from these and other studies on extensive reading seem to be mitigated due to methodological issues, which raise some questions about the effectiveness of extensive reading on L2 learning.…”
mentioning
confidence: 99%